1974
DOI: 10.1136/jcp.27.11.916
|View full text |Cite
|
Sign up to set email alerts
|

Plasma alkaline phosphatase isoenzymes in hepatobiliary disease

Abstract: By cellulose acetate or acrylamide gel electrophoresis it is possible to separate these alkaline phosphatase isoenzymes from serum: [anode] fast liver, slow liver, placenta/Regan, bone, intestine, bile [cathode]. Heat or chemical inhibition can confirm the differentiation.Normal adult serum always contains slow-liver isoenzyme, and sometimes bone isoenzyme: the latter is always present in serum of children. In hepatobiliary disease slow-liver isoenzyme was always increased: intestinal isoenzyme appeared in man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

1976
1976
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Kaplan and Rogers (1969) reported that, in their series, four patients with bone disease alone had a liver type main band, and in two of these there was no reason to suspect liver disease, while Sussman et al (1968) found that the AP isoenzymes of liver, bone, kidney, and intestine all moved with indistinguishable mobilities. More recently, Afonja and Baron (1974) found that normal adult serum always contained a slow 'liver' band and sometimes a bone band. Many of the discrepancies are accounted for by the fact that interpretation of the results obtained by electrophoretic separation of the alkaline phosphatase isoenzymes in serum has until now been largely subjective.…”
mentioning
confidence: 99%
“…Kaplan and Rogers (1969) reported that, in their series, four patients with bone disease alone had a liver type main band, and in two of these there was no reason to suspect liver disease, while Sussman et al (1968) found that the AP isoenzymes of liver, bone, kidney, and intestine all moved with indistinguishable mobilities. More recently, Afonja and Baron (1974) found that normal adult serum always contained a slow 'liver' band and sometimes a bone band. Many of the discrepancies are accounted for by the fact that interpretation of the results obtained by electrophoretic separation of the alkaline phosphatase isoenzymes in serum has until now been largely subjective.…”
mentioning
confidence: 99%
“…Alkaline phosphatases comprise a group of enzymes that catalyze the hydrolysis of a number of phosphate esters, in an alkaline environment, generating an organic radical and inorganic phosphate. Alkaline phosphatase is a membrane-bound metalloenzyme comprising a group of isoenzymes encoded by at least four different gene loci (Afonja and Baron, 1974). In healthy adults, this enzyme is mainly derived from the liver, bones and in a lesser amount from the intestine, placenta, kidneys, and leukocytes (Friedman, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Previous investigators, using different separating media, have identified the presence of a fast liver band in patients with liver disease (Fritsche and Adams-Park, 1974;Afonja and Baron, 1974), and this band may represent the slow moving isoenzyme noted in polyacrylamide gel electrophoresis (Fritsche and Adams-Park, 1974;Price and Sammons, 1974). De Broe et al, l975 found that the high molecular weight alkaline phosphatase with rapid migration on cellulose acetate electrophoresis corresponded to a membrane-vesicle fraction seen with electron microscopy in patients with cholestasis.…”
mentioning
confidence: 96%